Accelerated long‐term forgetting: Prognostic utility in familial Alzheimer's disease. (31st December 2021) - Alston, Duncan; O'Connor, Antoinette; Weston, Philip SJ; Lu, Kirsty; Pavisic, Ivanna M; Rice, Helen; Street, Rebecca E; Bowman, Erinna; Crutch, Sebastian J; Fox, Nick C
Abstract: Background: In Alzheimer's disease (AD), temporal lobe pathology begins years before onset of clinical symptoms 1 . Early detection of temporal lobe dysfunction would be valuable for trials. Accelerated long‐term forgetting (ALF) – failure to recall learnt material when the interval of testing is extended to days as opposed to the traditional interval of minutes – has been shown to be a sensitive measure of early cognitive change in AD. However, it is not clear if ALF can predict future progression. Here we investigate the prognostic utility of ALF by assessing whether baseline performance is associated with subsequent cognitive and clinical decline. Method: Thirty‐five at‐risk participants were recruited from UCL's Longitudinal Cohort Study of Familial Alzheimer's Disease (FAD). At baseline ALF was assessed by comparing recall performance at 7 days to performance after a 30‐minute interval. Visual (figure) and verbal (list and story) measures were used. Annual follow‐up visits included a detailed neuropsychological battery, mini‐mental state examination, Clinical Dementia Rating scale (CDR), measures of anxiety and depression and subjective memory decline. We tested for an association between baseline performance in ALF and rates of change in cognitive and clinical measures. Results: At baseline, mean time to estimated symptom onset (based on parental age at onset) for mutation carriers was 7.2 years (SD 4.5 years). Four mutation carriers became symptomatic (CDR>0); baseline performance in these cases was in the 5 th ‐23 rd percentiles for verbal measures of ALF. We will present the value of accelerated long‐term forgetting in predicting cognitive decline in this cohort. Conclusion: ALF is a feature of presymptomatic AD with potential utility in stratification and prognostication. References: 1. Bateman, R.J. et al. N. Engl. J. Med . 367, 795–804 (2012). 2. O'Connor, A. et al. Alzheimer's Res. Ther . 12, 1–9 (2020).